Pemberdayaan Warga Binaan melalui Pelatihan Keterampilan Kewirausahaan di Lapas Perempuan Kelas IIa Malang - Pahrany, Andi Daniah; Suwarman, Ramdhan Fazrianto; Pusawidjayanti, Kridha (Abdi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The activity focuses on fostering independence and personal development among inmates at the Women's Correctional Facility Class IIa Malang through entrepreneurial skills training. This training will equip inmates with basic entrepreneurial skills, including identifying business opportunities, business planning, marketing strategies, and managing small business operations. Additionally, it teaches practical techniques for starting and running sustainable businesses. The entrepreneurial training is conducted through interactive discussions and the presentation of best practices over two days. It involves 50 selected inmates based on their interest in entrepreneurship and nearing release dates. Data analysis is carried out using a qualitative descriptive method. The training results show that the food and beverage sector is the primary choice among participants, with 60% interested in starting businesses in this field. Participants are also deemed to have acquired the skills to identify market opportunities, design effective business plans, and implement operational and marketing strategies. This training is expected to have a significant positive impact on the inmates, helping them build a better future and reducing the risk of recidivism.